Scalable CAR-T production in a 2-litre perfusion stirred-tank bioreactor with automated harvesting and scale-down model characterisation - Springuel, Pierre; Silva Couto, Pedro; Stibbs, Dale J.; Szelwicki, Michal; Frangleton, Amanda; Schmidberger, Timo; George, Ajith; Slingsby, Fern; Bevan, Nicola; Ahmad, Asma; Legmann, Rachel; Dianat, Noushin; et al. (Frontiers in Bioengineering and Biotechnology, 2026)
The emergence of allogeneic, universal chimeric antigen receptor (CAR) T cell therapies requires intensified and scalable manufacturing workflows supported by representative scale-down models (SDMs) to enable efficient process development and future large-scale production of off-the-shelf therapies. Here, we present a 7-day CAR-T cell expansion process intensified via perfusion of serum-free medium in a 2 L Univessel® Single-Use stirred-tank bioreactor (STR), consistently achieving 30 × 106 cells/mL, corresponding to 113 ± 7 anti-CD19 CAR-T doses per batch. Parallel runs in 250 mL Ambr® 250 STRs conducted at equivalent volumetric power input (P/V) of ∼8.78 W/m3 demonstrated comparable process performance and final product quality, with univariate and multivariate analyses of cell growth, phenotype, cytotoxicity, and cytokine secretion validating the Ambr® 250 as a predictive SDM for the 2 L process. Integrating capacitance sensing in the 2 L STR enabled robust monitoring of viable cell concentrations in real-time, with strong correlation to offline measurements (R2 = 0.98). For downstream processing, the Ksep® 400 was used to automate CAR-T cell harvesting, concentration, and washing at the 2 L scale, achieving >90% product recovery and nine-fold volume reduction without impacting product quality attributes compared to manual methods. This study establishes a scalable CAR-T manufacturing workflow supported by a predictive SDM, providing an efficient platform for process development and scale-up to enable future large-scale production of allogeneic CAR-T cell therapies.